Rekomendasi Pemberian Beasiswa Bantuan Siswa Miskin Menggunakan Algoritma TOPSIS - Safii, Muhammad; Ningsih, Surya (STIKOM Tunas Bangsa Pematangsiantar, 2017)
Poor Student Assistance is a National Program that aims to assist poor students to go to school and gain access to appropriate educational services, prevent dropping out of school, help students meet the needs of learning activities, support the Nine Years Education Program (even to upper secondary) school programs sourced from the State Budget. Several outcomes from the evaluation and study of BSM Program implementation show the weakness of this program, that is related to the accuracy of targeting of BSM where there are still many non-poor households that receive BSM and the number of inadequate. The target of BSM Program beneficiaries is still weak where many BSM recipients are not from poor households and many students from poor households / households do not receive BSM benefits and are still manuals of the methods used in establishing BSM recipients. In this research used decision support system with Technique for Order Performance by Similarity to Ideal Solution method. With this method can provide the right decision for the proper in scholarship grants for poor students.